Human Development Analysis on Poverty Alleviation in South Sulawesi During the Covid-19 Pandemic - M. Aliem; M H Jamil; Rahmadanih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Poverty is one of the most fundamental issues in development. As a result, poverty reduction is one of the country's top priorities, not least for the administration of South Sulawesi Province. This is consistent with the first target of the Sustainable Development Goals (SDGs), which is to eliminate poverty in all of its manifestations everywhere. However, the poverty rate continues to fluctuate and even rises during the COVID-19 epidemic. Several studies have found that poverty is caused by social, economic, and cultural variables such as education, health, and money. As a result, the purpose of this research is to examine the impact of education, health, and the economy on poverty reduction in South Sulawesi. The data utilized is secondary data from the Central Statistics Agency's nationwide socioeconomic survey performed in 2020 and 2021. The SmartPLS program is used to do structural equation modeling-partial least squares (SEM-PLS) analysis on the data. The findings indicate that education, health, and the economy all have an impact on poverty in South Sulawesi. Health has a negative and considerable impact on poverty. The economy has a negative and considerable impact on poverty, but education has no such impact.